Reproductive and Endocrine Effects of p-Nonylphenol and Methoxychlor: A Review - Bandiera, Stelvio M. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2006)
The environmental endocrine disruptor hypothesis proposes a causal linkage between exposure to certain environmental pollutants and reproductive dysfunction. Although it is well recognized that hormonally active chemicals have the potential to adversely affect health, proof that environmental chemicals at ambient concentrations alter endocrine function in humans and wildlife is lacking. This review will focus on two man-made chemicals, p-nonylphenol, a surfactant product, and methoxychlor, a chlorinated pesticide, that are widely dispersed in the environment as a result of their broad uses in industrial processes and agriculture, respectively. Both chemicals bind to estrogen α and β receptors with low affinity and exhibit weak estrogenic activity in vitro and in vivo. p-Nonylphenol is inactivated if metabolized further, whereas the estrogenic effects of methoxychlor are derived in large part from its more active metabolites, especially dihydroxymethoxychlor. The review draws predominantly on the literature of the last 5 years and is organized to highlight 1. the sources and environmental fate of p-nonylphenol and methoxychlor, 2. effects of treatment with each chemical on endogenous hormone levels, 3. consequences of direct and developmental exposure on the female and male reproductive systems of experimental animals, and 4. effects on mammary gland development. The experimental evidence cited shows that methoxychlor and p-nonylphenol, at high dosages, adversely affects the mammalian reproductive system in females to a greater degree than males. Moreover, exposure during early development has profound and longer-lasting effects than adult exposure.
Keywords: p-nonylphenol